Exploring the Architecture of Research Data Management - Njagi, Pauline; Njoroge, Gitau (International Journal of Knowledge Content Development & Technology, 2025)
The study focused on model for effective research data management practices including metadata creation, design, storage, security, preservation, retrieval, sharing, and reuse. Data storage in a format that can be easily accessed, processed, and analyzed requires a functional architecture as datasets are often fragile and susceptible to storage malfunctions and advancing technology. The study used descriptive quantitative research design. Closed-ended questionnaire was the instrument of data collection. A total of 35 participants selected purposively were engaged to provide insight on study topic. The study used content validity to establish the degree to which the measure represented the paradigm of interest. Test retesting was done to establish questionnaire’s reliability which yielded a Cronbach Alpha result of 0.78 ascertaining reliability before questionnaires administering. Data was analyzed using statistical analysis for social sciences and result presented in pie-chart. The finding informs of widespread use or plan to adopt the “Repository” data architecture model reflecting a widespread understanding among participants of its applicability for enabling research data management practices in academic libraries. However, the study recommends for further studies on repository model standards in academic libraries and blackboard functionality and effectiveness in research data management.